The concept of the self in the words of al-Imam al-Ghazali and its relationship to knowledge acquisition - Ssuna, Salim (Pusat Akidah dan Keamanan Global, Faculti Pengajian Islam, UKM, 2019)
The spiritual life in Islam begins with the inner warfare against the ego which is distracted and polluted by the materials world. The lower self has a tendency of dragging the human down into arrogance and vice. The sincere and knowledgeable worshipper can achieve the purity of soul which enables him to attain God's proximity. The self has been given various names in numerous civilizations signifying its position in human life. This study will critically evaluate iman al-Ghazali’s views on the self and how it relates to the acquisition knowledge in producing a balanced human being. This is a qualitative study and it used the interpretation method approach. Data collection entirely depend on library research by referring to relevant documents written by imam al-Ghazali and other related studies. Data analysis was in form of descriptive textual analysis of the concept of the self in the words of al-Ghazali and how it is related to knowledge acquisition. The findings showed that the self is an important aspect of a human being which must be equipped with the necessary knowledge in order to create a strong link to its creator to play its role as a vicegerent diligently. This self will be expedient to other human beings and other creatures of Allah the Almighty.